For Part 1:
To find the value of y when x = 0, we can substitute x = 0 into the equation and solve for y:
3(0) - 2y = 6
-2y = 6
y = -3
Therefore, when x = 0, y = -3.
For Part 2:
To find the value of y when x = 2, we can substitute x = 2 into the equation and solve for y:
3(2) - 2y = 6
6 - 2y = 6
-2y = 0
y = 0
Therefore, when x = 2, y = 0.
For Part 3:
To find the value of y when x = -2, we can substitute x = -2 into the equation and solve for y:
3(-2) - 2y = 6
-6 - 2y = 6
-2y = 12
y = -6
Therefore, when x = -2, y = -6.
The completed table is as follows:
x | y
------------------
0 | -3
2 | 0
-2 | -6
Now we can graph the equation 3x - 2y = 6:
Plot the points (0, -3), (2, 0), and (-2, -6) on the coordinate plane and draw a straight line passing through these points.
The graph of the equation is a straight line that passes through the points (0, -3), (2, 0), and (-2, -6).
Complete the table for the equation 3x−2y=6, and graph the equation.
Question content area bottom left
Part 1
x
y
0
negative 3−3
Part 2
22
0
Part 3
−2
enter your response here
1 answer